Dual roles of methoprene-tolerant gene TaMet in male molting and female reproduction of the tomato leafminer, Tuta absoluta (meyrick) - Zhang, Tingwei; Xu, Kai; Liu, Deqian; Ma, Hang; Liu, Wenbiao; Yang, Wenjia (Frontiers in Physiology, 2024)
The tomato leafminer (Tuta absoluta) is a highly destructive global quarantine pest. The methoprene-tolerant (Met) protein, a member of the bHLH/PAS family of transcription factors, forms complexes with other family members to transduce the juvenile hormone signal, which regulates insect growth and development. However, the functions of the TaMet gene have rarely been studied in T. absoluta. Herein, we investigated the significance of TaMet in T. absoluta. Spatiotemporal expression analysis revealed that TaMet exhibited comparable expression patterns in males and females, with high expression levels during the early pupal and early adult stages. TaMet was predominantly expressed in the female ovary and male wing. TaMet knockdown impaired ovarian development in female adults, causing irregular arrangement and increased spacing of the egg epithelial cells in the ovary. Silencing TaMet also led to a 67.25% reduction in female spawning and a 67.21% decrease in the offspring hatching rate. Furthermore, the vitellogenin content was significantly diminished, and the expression levels of vitellogenin (Vg) and vitellogenin receptor (VgR) genes were significantly downregulated. In contrast, silencing TaMet in 3-day-old male pupae resulted in an 80% mortality rate and various phenotypic abnormalities, including body melanism, molting defects, and wing deformities. Moreover, the expression levels of wing development and chitin metabolism genes decreased significantly after knocking down TaMet. Our results indicate that TaMet plays a significant dual role in male molting and female reproduction of T. absoluta.